2020
DOI: 10.3390/microorganisms8071059
|View full text |Cite
|
Sign up to set email alerts
|

Lung Microbiome Participation in Local Immune Response Regulation in Respiratory Diseases

Abstract: The lung microbiome composition has critical implications in the regulation of innate and adaptive immune responses. Next-generation sequencing techniques have revolutionized the understanding of pulmonary physiology and pathology. Currently, it is clear that the lung is not a sterile place; therefore, the investigation of the participation of the pulmonary microbiome in the presentation, severity, and prognosis of multiple pathologies, such as asthma, chronic obstructive pulmonary disease, and interstitial lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…Asthma and allergic rhinitis are two conditions that, either when occurring together or separately, impart a health and economic burden to persons and society [ 6 , 7 , 15 , 95 , 96 , 97 ]. Emerging evidence has suggested that both airway diseases are intimately linked to alterations of the nasal bacteriome [ 45 , 52 , 56 , 93 , 98 , 99 , 100 , 101 , 102 ]. In this cross-sectional study, we apply 16S rRNA amplicon HTS to a large cohort of individuals from northern Portugal with asthma or allergic rhinitis (with and without comorbid asthma) and healthy controls to characterize their nasal bacteriotas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma and allergic rhinitis are two conditions that, either when occurring together or separately, impart a health and economic burden to persons and society [ 6 , 7 , 15 , 95 , 96 , 97 ]. Emerging evidence has suggested that both airway diseases are intimately linked to alterations of the nasal bacteriome [ 45 , 52 , 56 , 93 , 98 , 99 , 100 , 101 , 102 ]. In this cross-sectional study, we apply 16S rRNA amplicon HTS to a large cohort of individuals from northern Portugal with asthma or allergic rhinitis (with and without comorbid asthma) and healthy controls to characterize their nasal bacteriotas.…”
Section: Discussionmentioning
confidence: 99%
“…The airway microbiota can influence host metabolism and homeostasis, including epithelial cell growth and repair, and inflammatory and immune responses, thereby impacting chronic disease onset and progression [ 34 , 39 , 45 , 99 , 100 , 101 , 102 , 109 , 117 , 118 , 119 ]. Compared to healthy controls, our PICRUSt2 analyses predicted 50–55 pathways upregulated in rhinitic patients ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing bacterial 16S rRNA amplicons, even in low biomass samples such as bronchoalveolar lavage fluid (BALF), represents a powerful tool to overcome a critical barrier to progress in understanding the role of complex microbial communities in the respiratory tract. Recent data suggest the endogenous airway microbiota play a fundamental role in establishing health vs. diseased states with the microbiota having a symbiotic relationship with the host, by providing a barrier function against pathogenic species, regulating cell growth, promoting healing, and modulating immune responses ( 11 , 12 ). While lower airways of healthy individuals have traditionally been considered sterile because of negative culture results, sequencing of microbial 16S rRNA amplicons has revealed a rich and diverse population of bacterial species previously missed ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lung microbiome of healthy individuals is characterized by a low bacterial load and a high species diversity, with the most common genera being Prevotella , Streptococcus , Veillonella , Neisseria , Haemophilus , and Fusobacterium [ 28 , 29 ]. In this study, Prevotella was found among the under-represented species during infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%